Portfolio Choice and Saving in an Optimal Consumption-Leisure Plan - Cox, J. C. (Review of Economic Studies, 1975)
Journal Article Portfolio Choice and Saving in an Optimal Consumption-Leisure Plan Get access J. C. Cox J. C. Cox University of Massachusetts Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 1, January 1975, Pages 105–116, https://doi.org/10.2307/2296824 Published: 01 January 1975